Implementation of the Independent Curriculum in Elementary Education: A Case Study of Fourth-Grade Teaching Practices in Indonesia - Nurma Yuntika Tolodo; Nashrullah Nashrullah; Sisriawan Lapasere; Zulnuraini Zulnuraini; Dyah Rahmawati; Surahman Wilade (Papanda Publisher, 2026)
The Independent Curriculum represents Indonesia's response to pandemic-induced learning disruptions, emphasizing learner-centered pedagogy and differentiated instruction. However, implementation at specific grade levels, particularly fourth grade as a critical transition point, remains insufficiently documented. This study examined Independent Curriculum implementation in fourth grade at SD Inpres 1 Tondo, focusing on learning planning, instructional implementation, and assessment practices. A qualitative descriptive case study was conducted over three months (August-October 2025) with one purposively selected fourth-grade teacher. Data were collected through non-participant classroom observations, semi-structured interviews, and document analysis of teaching modules and assessment instruments. Data analysis employed Miles et al.'s interactive model involving data reduction, display, and conclusion drawing. Findings revealed comprehensive teacher understanding of curriculum principles and systematic learning planning incorporating diagnostic assessments and differentiated strategies. Implementation demonstrated student-centered approaches and varied media utilization. However, persistent challenges emerged including limited student engagement during transition periods, inadequate infrastructure constraining material distribution, textbook variation complicating delivery, insufficient family support, and assessment complexity in holistic evaluation. Teacher adaptation of standardized instruments reflected contextual responsiveness but raised standardization concerns. Independent Curriculum implementation quality depends on dynamic interactions among teacher competence, institutional resources, family involvement, and systemic support. Successful realization requires comprehensive ecosystem approaches addressing professional development, infrastructure investment, parent engagement, and assessment literacy simultaneously.